A CRITICAL STUDY OF THE IMPLEMENTATION OF DIVERSION IN RESOLUTION OF ARCHERY-RELATED CRIMES WITH CHILD OFFENDERS AT BIMA POLICE - Nur Ilmi Putri Febriyanti; Muchamad Iksan; Kuswardani (Bengkoelen Justice : Jurnal Ilmu Hukum, 2026)
This writing aims to find out the application of diversion by investigators of diversion by resort police Bima city to archery-related crimes with child actors. The approach used by the author in this research is a case approach and a social legal approach with the type of empirical legal research.  Types and sources of data used are primary data and secondary data. The results of research on the application of diversion by Bima City Police investigators on archery-related crimes with child offenders can be successfully carried out if there is an agreement in deliberation between the victims, perpetrators and related parties. The factors causing the failure of diversion by investigators from resort police Bima city are due to the lack of understanding of the victim and the paradigmatic hegemony that occurs in the community who think that the appropriate place for children who are in conflict with the law is prison to provide a deterrent effect so that children do not repeat the same actions.